Mild deglobalization: Foreign investment screening and cross-border investment - Vera Eichenauer; Feicheng Wang (Kiel Institute for the World Economy (IfW Kiel), 2024)
Openness to foreign investments is associated with risks. To mitigate these risks, many high-income countries have strengthened the control of foreign investments over the last decade in an increasing number of sectors considered critical. Investment screening distorts the market for cross-border investments in controlled sectors, which might lead to unintended economic effects. This is the first cross-country panel study to examine the economic effects of investment screening mechanisms. We combine deal-level data on cross-border mergers and acquisitions (M&A) for the period 2007-2022 with information on sectoral investment screening. Using a staggered triple difference design, we estimate a reduction of 11.7 to 16.0 percent in the number of M&A in a newly screened sector. The effects are driven by minority acquisitions and deals involving a foreign government or state-owned enterprises or US firms as investors. There is no reduction in the number of deals within the EU/EFTA, most of which are not subject to screening. The findings call policymakers' attention to weighing the benefits of national security and the economic costs of introducing investment screening.
Keywords: F21; F52; G34; 330; foreign direct investments; national security; M&A; investment screening; global capital allocation; geoeconomic fragmentation; deglobalization